American Medical Society for Sports Medicine Position Statement on the Care of the Athlete and Athletic Person With Diabetes. Issue 1 (January 2022) - Trojian, Thomas; Colberg, Sheri; Harris, George; Oh, Robert; Dixit, Sameer; Gibson, Margaret; Corcoran, Matthew; Ramey, Lindsay; Berg, Philip V.
Abstract : Abstract: The American Medical Society for Sports Medicine (AMSSM) developed this position statement to assist physicians and other health professionals in managing athletes and active people with diabetes. The AMSSM selected the author panel through an application process to identify members with clinical and academic expertise in the care of active patients with diabetes. This article reviews the current knowledge and gaps regarding the benefits and risks of various types of exercise and management issues for athletes and physically active people with diabetes, including nutrition and rehabilitation issues. Resistance exercises seem to be beneficial for patients with type 1 diabetes, and the new medications for patients with type 2 diabetes generally do not need adjustment with exercise. In preparing this statement, the authors conducted an evidence review and received open comment from the AMSSM Board of Directors before finalizing the recommendations. Abstract : Supplemental Digital Content is Available in the Text.